2009
DOI: 10.1142/s021952590900209x
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Scale-Free Networks in Markets

Abstract: Financial markets are complex systems, all the information scattered around the market is fairly and dynamically reflected in the current prices. However, it is difficult to understand the dynamics of markets merely by traditional analyzing methods. We here propose a new concept inspired by complex networks to study the trading behavior and the dynamics of markets. A web-based platform for prediction market which trades the political futures contracts is built to monitor the trading behavior among the human pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In previous studies [22,26], we demonstrated that the transaction networks resulting from two parallel market experiments on our platform possess scale-free, hierarchical and disassortative structure. However, due to the low statistics in earlier experiments, we can not make solid conclusions for neither the dynamics of network growth nor the relation between individual wealth and network structure.…”
Section: Results and Analysismentioning
confidence: 67%
“…In previous studies [22,26], we demonstrated that the transaction networks resulting from two parallel market experiments on our platform possess scale-free, hierarchical and disassortative structure. However, due to the low statistics in earlier experiments, we can not make solid conclusions for neither the dynamics of network growth nor the relation between individual wealth and network structure.…”
Section: Results and Analysismentioning
confidence: 67%
“…We consider an artificial financial market composed of N = 100 agents, whose pattern of interactions is captured by a Barabasi-Albert scale-free network [36] with average degree 4. A scalefree network topology has been selected as it is typically observed both in financial networks and in other social or biological contexts [37][38][39][40]. In agreement with past works, the fundamental price p f (t) is taken as a realization of a geometric Wiener process [30,31].…”
Section: Numerical Setupmentioning
confidence: 99%
“…Wang et al (2008) study the network topology of a prediction market which is an experimental futures exchange. Tseng et al (2009) propose an agent-based model with "zero-intelligence" traders under the continuous double auction market mechanism to explain the power-law degree distribution of the trading network. Tseng et al (2010a) investigate the trading network of a prediction market to study the dynamics of wealth accumulation.…”
Section: Introductionmentioning
confidence: 99%